2012
DOI: 10.1084/jem.20111644
|View full text |Cite
|
Sign up to set email alerts
|

Serum from patients with SLE instructs monocytes to promote IgG and IgA plasmablast differentiation

Abstract: Monocytes exposed to serum from SLE patients promote B cell differentiation to IgG and IgA plasmablasts dependent on BAFF and IL-10 or APRIL, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 70 publications
8
83
0
1
Order By: Relevance
“…In these pathologies, elevated type I IFN levels are thought to induce hyperactivation of the immune response based on increased antigen presentation by cDCs and IFN-DCs, increased activation of professional cytotoxic cells and stimulation of auto-antibodies production, which all play an important role in the loss of tolerance and persistent autoimmune reaction. This close relationship was demonstrated in a recent paper by showing that SLE patient serum could induce the differentiation of monocytes into DCs in an IFN-dependent manner, and that these DCs could stimulate naive and memory B cells to differentiate into IgG-and IgA-plasmablasts resembling those found in the blood of SLE patients [195]. Elevated levels of type I IFNs were also recognized as important pathogenic factors for the increased risk of atherosclerosis described in SLE patients because of the above described detrimental vascular effects [40].…”
Section: Pdc-derived Type I Ifns In Autoimmunitymentioning
confidence: 53%
“…In these pathologies, elevated type I IFN levels are thought to induce hyperactivation of the immune response based on increased antigen presentation by cDCs and IFN-DCs, increased activation of professional cytotoxic cells and stimulation of auto-antibodies production, which all play an important role in the loss of tolerance and persistent autoimmune reaction. This close relationship was demonstrated in a recent paper by showing that SLE patient serum could induce the differentiation of monocytes into DCs in an IFN-dependent manner, and that these DCs could stimulate naive and memory B cells to differentiate into IgG-and IgA-plasmablasts resembling those found in the blood of SLE patients [195]. Elevated levels of type I IFNs were also recognized as important pathogenic factors for the increased risk of atherosclerosis described in SLE patients because of the above described detrimental vascular effects [40].…”
Section: Pdc-derived Type I Ifns In Autoimmunitymentioning
confidence: 53%
“…These findings indicated a potential role for circulating DNA-containing ICs in autoantibody production in SLE patients. Consistently, studies of SLE patients revealed that exposure of healthy monocytes to SLE serum resulted in the generation of dendritic cells that were endowed with a unique ability to promote IgG and IgA plasmablast differentiation (17)(18)(19). Combining these findings prompted us to hypothesize that the SLE plasma, especially circulating DNA-containing ICs, might induce anti-dsDNA autoantibody and, thus, maintained production of anti-dsDNA autoantibody in SLE patients.…”
mentioning
confidence: 81%
“…B cells were isolated from peripheral blood of healthy donors and cultured with CpG (a TLR9 agonist) and/or cytokine cocktails including IL-2, IL-6, and interferon-alpha (IFN-a), which are known to provide conditions for effective plasmablast differentiation (Jego et al, 2003;Joo et al, 2012). Indeed, we detected CD27 hi CD38 + putative plasmablasts after culture with CpG, while concomitant treatment with CpG and cytokine cocktails induced a greater frequency of an additional population of CD27 int CD38 + cells as well as CD27 hi CD38 + cells ( Figure 6A).…”
Section: Plasmablast-derived Il-10 Inhibits Dendritic Cell Function Tmentioning
confidence: 99%